Developments of employment by broad age-groups in Poland in the years 1998–2008. Do their determinants differ? - Grabowska, Izabela (Studia Demograficzne, 2014)
The latest Eurostat projections show that both population and labour force ageing change employment profiles by age in the European Union countries even in case of an increase in labour force participation and employment (The 2012 Ageing Report). My research question is how basic individual (such as age, education, household position, place of residence) and contextual characteristics (such as the business cycle and the regional labour market situation) influence on employment opportunities in Poland. I test whether the impact of different factors varies with age, which has been categorized to reflect different stages of the life course: youth and young adults (15–29 years old), prime aged (30–54 years old), and older workers (for women: 55–59, for men: 55–64). To answer the research question three types of multilevel logistic models were applied: (a) general models with age as one of the basic determinants, (b) models for each age group for non-agriculture and agriculture. The data used come from the Polish Labour Force Survey (BAEL) of the years 1998–2008 and regional labour market data. The analysis reveals that there are differences in influence of individual and context variables on employment odd ratios between age groups, sex and employment sectors.